Warfarin or Acenocoumarol: Which Is better in the Management of Oral Anticoagulants? - Barcellona, Doris; Vannini, Maria Luigia; Fenu, Lara; Balestrieri, Cinzia; Marongiu, Francesco (Thrombosis and Haemostasis, 1998)
Warfarin is employed more frequently than acenocoumarol because of its longer half-life (36 h), theoretically providing more stable anticoagulation, and avoiding factor VII fluctuations that potentially occur during acenocoumarol treatment (half-life 10 h).The aim of our study was to compare acenocoumarol with warfarin in the same group of 103 patients who started oral anticoagulation with acenocoumarol and then changed to warfarin. In these patients we compared the previous period of six months on acenocoumarol treatment (July-December 1996) with a new six-month period on warfarin (July-December 1997). We wished to know whether warfarin could improve the quality and the stability of oral anticoagulation of our patients and whether there was a difference between the two drugs in the weekly mean dose per patient. Moreover in order to detect the possible daily fluctuation of factor VII, we evaluated a further group of 54 patients. A subgroup of these patients was treated with warfarin while another received acenocoumarol.In the first group of patients, 1,158 and 1,064 PTs were carried out with acenocoumarol and warfarin, respectively. The percentage of PTs in the therapeutic range was 59% with acenocoumarol and 62% with warfarin (p = 0.4). The mean number of visits per patient was 12 and 11, and the mean number of visits in the therapeutic range was 7 and 7, respectively. The last check in file method did not show any difference between the two drugs. Overdose states were 51 (4.4%) with acenocoumarol and 30 (2.8%) with warfarin (p = 0.4). A good correlation (r = 0.92) was found between the acenocoumarol and the warfarin weekly mean dose. The mean warfarin/acenocoumarol weekly dose ratio was 2.08 (range: 1.25-3.30; CI 95%: 1.99-2.16).In the second group of patients, factor VII levels with both drugs were higher 24 h after administration than 16 h after, showing that their daily fluctuation was independent of the drug’s half-life, since factor VII levels in patients with a low vitamin K intake were not increased.Our results showed that warfarin did not appear to be better than acenocoumarol in the performance of an Anticoagulation Clinic in terms of PTs within the therapeutic range per patient. It seems that the behaviour of factor VII was affected by the intake of vitamin K rather than by the short half-life of acenocoumarol.